The effects of variable riverine inputs and seasonal shifts in phytoplankton communities on nitrate cycling in a coastal lagoon - Zilius, Mindaugas; Barisevičiūtė, Rūta; Bonaglia, Stefano; Klawonn, Isabell; Lorre, Elise; Politi, Tobia; Vybernaite-Lubiene, Irma; Voss, Maren; Overlinge, Donata; Bukaveckas, Paul A. (Frontiers in Marine Science, 2024)
Estuarine systems, being situated at the interface between land and marine environments, are important sites for nitrate (NO3–) retention and processing due to large inputs, long retention time, and high biogeochemical activity. However, it remains uncertain how pelagic and benthic processes control NO3– cycling and how the relative importance of these processes is affected by seasonal changes in estuarine conditions. We measured the suite of processes governing NO3– cycling in the Curonian Lagoon (Southeast Baltic Sea) during two time periods representing spring and summer conditions. We show that in spring, benthic dissimilatory and assimilatory NO3– processes prevailed, while in summer, pelagic assimilatory processes dominated. During spring, warming temperatures and riverine nitrogen (N) inputs were associated with the onset of diatom blooms. N assimilation by diatoms resulted in the delivery of particulate organic N and organic matter to the benthos, resulting in greater denitrification in the sediments and a flux of NO3– from the water column to the sediments. In summer, phytoplankton blooms of buoyant cyanobacteria and high rates of assimilatory uptake dominated, resulting in greater particulate organic N export from the lagoon into the sea. Given the low dissolved inorganic N concentrations in summer, high uptake indicates that the pelagic community possessed a nutritional strategy to efficiently utilize multiple N forms at high rates. Overall, our findings show that diatom-dominated communities foster strong benthic-pelagic coupling, whereas cyanobacteria dominance is associated with pelagic-based N cycling. While this study sheds new light on mechanisms of NO3– retention in the Curonian Lagoon, further spatiotemporal resolution is recommended to better represent the variability in rates and to include other Baltic lagoons for a comprehensive understanding of N cycling in shallow estuarine systems.